Digital Information and Communication Technologies: challenges and possibilities for integration in school Physical Education - Faganello Gemente, Florence Rosana; Salles da Silva, Ana Paula; Matthiesen, Sara Quenzer [UNESP] (Editora Univ Leopoldlanum, 2020)
This essay analyzes the insertion of Digital Information and Communication Technologies in Physical Education classes at school. To this end, we present different reflections on the challenges related to teacher training, the conflict between theoretical and practical classes, infrastructure, and teaching conditions. It also addresses different paths so that Digital Information and Communication Technologies can be integrated in Physical Education classes at school in a critical, creative and ethical way. Finally, even though the challenges pose real obstacles, the existing initiatives indicate that the use of Digital Information and Communication Technologies is diverse and has a relevant training potential that can no longer be ignored.
Keywords: Physical Education; School; Digital Information and Communication Technologies